Comparison of medical and industrial X-ray computed tomography for non-destructive testing - du Plessis, Anton; le Roux, Stephan Gerhard; Guelpa, Anina (Case studies in nondestructive testing and evaluation, 2016)
•Direct comparison between medical and microCT for industrial NDT.•Challenging test objects even for typical microCT up to 225 kV.•Accuracy of microCT demonstrated as expected for all four test cases.•Medical CT shows reasonable results in some applications.•Indicates feasibility of fast, cost effective scanning for macro features using medical scanning. Industrial X-ray computed tomography (CT) is an emerging laboratory-based non-destructive testing technique used in a variety of applications for samples ranging from 1 mm to usually 300 mm in diameter. Usually, microCT scanners are used for industrial non-destructive testing due to the superior resolution possible compared to medical CT scanners, but it is not generally known that medical CT scanners can produce reasonable results when high resolution is not needed. As demonstrated in this case study of very dense objects, far shorter scan time is required, compared to conventional laboratory industrial CT systems, consequently being a better solution for applications such as quick scout-scans, high throughput applications and larger objects. This case study makes use of four typical industrial test objects, specifically chosen as candidates which would be expected to be too dense for relatively low-voltage medical scanners. The respective test objects were scanned with both medical and microCT scanners and the results compared for the purpose of industrial non-destructive analysis. The test objects are a steel turbine blade, a titanium casting, a concrete cylinder with aggregate stones and porosity, and a concrete block with metal fiber reinforcement.